2020
DOI: 10.1108/mrr-03-2020-0141
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the role of HRM practices on service innovation: empirical evidence from UAE government agencies

Abstract: Purpose Government agencies are trying to develop strategies to improve their innovative activities. However, due to many challenges and obstacles, employees are reluctant to perform innovatively in such agencies. Human resource management (HRM) practises and an appropriate culture can help to improve service innovation. However, empirical evidence to prove this relationship is insufficient particularly in the government sector. Thus, this study aims to empirically analyses the effect of HRM practises and inno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 138 publications
1
18
0
1
Order By: Relevance
“…In particular, studies in the UAE have found that HR practices have positive effects on organisational culture, job satisfaction and commitment from the local and expatriate employees (Waxin & Bateman, 2016). Human resource practices enhanced the innovation culture and services of UAE's government agencies (Alosani, Al-Dhaafri, & Abdulla, 2021) and proved their effectiveness in the UAE's education sector. Although Adekoya, Ajonbadi, Okorie and Jimoh (2021) found that there is still need for the reinforcement of HRM regarding the facilitation of work-life balance policies for talent attraction and retention purposes in UAE education sector.…”
Section: Training and Development: It Comprises The Formalmentioning
confidence: 99%
“…In particular, studies in the UAE have found that HR practices have positive effects on organisational culture, job satisfaction and commitment from the local and expatriate employees (Waxin & Bateman, 2016). Human resource practices enhanced the innovation culture and services of UAE's government agencies (Alosani, Al-Dhaafri, & Abdulla, 2021) and proved their effectiveness in the UAE's education sector. Although Adekoya, Ajonbadi, Okorie and Jimoh (2021) found that there is still need for the reinforcement of HRM regarding the facilitation of work-life balance policies for talent attraction and retention purposes in UAE education sector.…”
Section: Training and Development: It Comprises The Formalmentioning
confidence: 99%
“…The main channels by which organizations can influence their human resources are HRM activities. The influence of HRM practices on service innovation has been examined in several studies (Alosani et al, 2020;Chen, 2018;Ardito et al, 2017;Bamber et al, 2017;Engelman et al, 2017;Escriboa-Carda et al, 2017;Chang et al, 2011) and the direct relation between HRM practices and service innovation (Waheed et al, 2019;Ardito and Messeni, 2017;Akbari and Monzavi, 2015). Research on this subject, however, remains immature (Tajeddini et al, 2020;Ardito et al, 2017) and empirical studies focusing on this subject remain scarce (Bonfanti et al, 2018;Losey, 2012) in the government sector in particular (AlMarzouqi, 2019;Battistelli et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They explain that the activities of human resources management are the procedures through which organizations can effectively exploit the ability of employees and provide them with opportunities for creativity. HRM practices is the key component of development and growth, it supports organizations in their decision-making, teamwork, empowerment, collaboration (Alosani et al, 2020), and organizational trust (Chang and Lee, 2020;Chivandi and Maziriri, 2018). This issue will be positively reflected in the promotion of knowledge and employee awareness behaviors, which in turn lead to improving their capacity to innovate (Favoreu et al, 2019).…”
Section: Human Resource Management Practicesmentioning
confidence: 99%
See 2 more Smart Citations